2014
DOI: 10.1155/2014/649016
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Associated with Hypercholesterolemia following Thyroid Hormone Withdrawal in Thyroidectomized Patients

Abstract: Thyroid hormone withdrawal (THW) for postoperative radioiodine adjuvant therapy or diagnostic radioiodine whole body scan in patients with differentiated thyroid cancers results in acute thyroid hormone deficiency and abnormal lipid profiles. To better clarify the clinical pattern of dyslipidemia occurring after THW, we retrospectively analyzed the association between serum total cholesterol level after THW and various clinical factors in a total of 61 patients who underwent total thyroidectomy due to papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to show that normal TSH levels are associated with increased hypercholesterolemia risk in DTC patients receiving levothyroxine after total thyroidectomy. Although changes in the serum lipid levels during thyroxine withdrawal after total thyroidectomy have been assessed in some studies, the risk of hypercholesterolemia during levothyroxine therapy has not been [22,23,24,25]. Owing to the fact that thyroid cancers are detected early these days, leading to a low risk, and that most DTC patients have a favorable clinical course [26], the unsuppressed range of TSH may be applied to many such cases according to current management guidelines [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to show that normal TSH levels are associated with increased hypercholesterolemia risk in DTC patients receiving levothyroxine after total thyroidectomy. Although changes in the serum lipid levels during thyroxine withdrawal after total thyroidectomy have been assessed in some studies, the risk of hypercholesterolemia during levothyroxine therapy has not been [22,23,24,25]. Owing to the fact that thyroid cancers are detected early these days, leading to a low risk, and that most DTC patients have a favorable clinical course [26], the unsuppressed range of TSH may be applied to many such cases according to current management guidelines [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…19,29,30,42,55,71,79,102 The association between serum FT4 and MetS diagnosis was not always found. However, when this association occurred, it was reported as positive (with higher serum FT4 levels) in some studies, 38,53,102 while negative in others. 24,54,95 Higher levels of serum FT3 related to MetS were also detected in some studies.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 97%
“…In addition, the fact that other confounding molecular cues, including elevated levels of insulin-like growth factors [ 14 ], leptin [ 15 ], hormones [ 16 ] and cytokines [ 17 ] were not adjusted in studies, could also result in the divergent interpretations for prognosis after hepatectomy between lean and obese subjects. With a causal link between BMI and total cholesterol level in many cancers, it was interestingly found an inverse correlation between preoperative total cholesterol levels and clinical postoperative outcomes of HCC patients in several studies [ 18 - 20 ]. Further examination in these studies suggested that poorer surgical outcome in patients with lower preoperative total cholesterol level and BMI might be caused by long-term liver dysfunction and malnutrition implying the potential role of lipid composition for determination of operative outcomes in HCC patients.…”
Section: Introductionmentioning
confidence: 99%